Enhancing Executive Functions Through Social Interactions: Causal Evidence Using a Cross-Species Model - Perry, Rosemarie E.; Braren, Stephen H.; Rincón-Cortés, Millie; Brandes-Aitken, Annie N.; Chopra, Divija; Opendak, Maya; Alberini, Cristina M.; Sullivan, Regina M.; Blair, Clancy (Frontiers in Psychology, 2019)
It has long been theorized that humans develop higher mental functions, such as executive functions (EFs), within the context of interpersonal interactions and social relationships. Various components of social interactions, such as interpersonal communication, perspective taking, and conforming/adhering to social rules, may create important (and perhaps even necessary) opportunities for the acquisition and continued practice of EF skills. Furthermore, positive and stable relationships facilitate the development and maintenance of EFs across the lifespan. However, experimental studies investigating the extent to which social experiences contribute causally to the development of EFs are lacking. Here we present experimental evidence that social experiences and the acquisition of social skills influence the development of EFs. Specifically, using a rat model, we demonstrate that following exposure to early-life adversity, a socialization intervention causally improves working memory in peri-adolescence. Our findings combined with the broader literature promote the importance of cultivating social skills in support of EF development and maintenance across the lifespan. Additionally, cross-species research will provide insight into causal mechanisms by which social experiences influence cognitive development and contribute to the development of biologically-sensitive interventions.